Case Report: Insulinoma Presenting as Excessive Daytime Somnolence - Yu, Zhennan; Wang, Yongliang; Sun, Yaqi; Wang, Yumei; Tian, Yayun; Ma, Qinying; Fu, Ying (Frontiers in Endocrinology, 2021)
Unrecognized insulinoma remains an intractable clinical challenge because the symptoms are in most cases misattributed to other disorders.We present the case of a 14-year-old girl who had a 3-month history of recurrent episodes of excessive daytime sleepiness and behavioral disorders during sleep. Insulinoma is a rare neuroendocrine tumor that causes inappropriate release of insulin,resulting in episodes of hypoglycemia. It classically present with autonomic sympathetic symptoms. These symptoms resolve promptly following glucose administration.The patient underwent successful resection of the tumor, and his symptoms showed complete resolution.